2015
DOI: 10.1055/s-0034-1380191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Toolbox of Clickable Rhodamine B Derivatives

Abstract: An efficient method for the large-scale preparation of rhodamine B clickable derivatives has been developed. Starting from inexpensive rhodamine B as the starting material it was possible to functionalize the carboxylic functionality of rhodamine B with an azide, a strained-alkyne, a substituted triphenylphosphine, a thiol, and a maleimide. Through the synthetic strategy it was possible to obtain stable and pure clickable rhodamine compounds that can be readily used not only for chemoselectively probing biomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
(7 reference statements)
0
6
0
Order By: Relevance
“…Boc-piperazine (39) 72 (1 equiv) was dissolved in ACN. Triethylamine (2.5 equiv) and the acid chloride (3 equiv) were added dropwise resulting in an opaque solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boc-piperazine (39) 72 (1 equiv) was dissolved in ACN. Triethylamine (2.5 equiv) and the acid chloride (3 equiv) were added dropwise resulting in an opaque solution.…”
Section: Methodsmentioning
confidence: 99%
“…EDC-HCl (1 equiv) and NHS (1 equiv) were added and the solution was stirred for 16 h to form the activated ester. N,N-Diisopropylethylamine (1 equiv) and Boc-piperazine ( 37 ) 72 (1 equiv) were added, and the solution was stirred at room temperature for 4 h. The ACN was evaporated under reduced pressure, and the residue was dissolved in DCM. The DCM solution was washed with water, saturated NaHCO 3 solution, and brine and subsequently dried with anhydrous MgSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…This synthetic strategy has been recently reported by our research group and revealed to be very efficient, leading to high quantities of product with high purity. 34 The detailed synthesis and characterization of Rhodamine B-MPA is reported in the Supporting Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1-Bromo-2-(2-bromoethyl)benzene, 35 1-bromo-2-(2-bromopropyl) benzene, 36 1-bromo-3-(2-bromoethyl)benzene, 37 1-bromo-3-(3bromopropyl)benzene, 38 1-bromo-4-(2-bromoethyl)benzene, 39 4-bromophenethyl methanesulfonate, 40 and 3-(4-bromophenyl) propyl methanesulfonate, 41 trans-2-(1-piperazinyl)cyclohexanol, 1 and tert-butyl piperazine-1-carboxylate 42 were synthesized according to previous reports. The mixture was stirred under reflux for 54 h. After cooling to room temperature, insoluble materials were removed by filtration and the filtrate was concentrated in vacuo.…”
Section: Methodsmentioning
confidence: 99%